Effects of silver nanoparticles to soil invertebrates: Oxidative stress biomarkers in Eisenia fetida. (April 2015) - Gomes, Susana I.L.; Hansen, Ditte; Scott-Fordsmand, Janeck J.; Amorim, Mónica J.B.
Abstract: Silver nanoparticles (Ag-NPs) are among the most produced NPs worldwide having several applications in consumer products. Ag-NPs are known to cause oxidative stress in several organisms and cell lines, however comparatively less information is available regarding their effects on soil living invertebrates. The purpose of this study was to investigate if Ag-NPs cause oxidative stress on soil invertebrates. The model soil species Eisenia fetida was used. Our results showed that total glutathione (TG) is the first mechanism triggered by Ag-NPs, followed by glutathione peroxidase (GPx) and glutathione reductase (GR), however oxidative damage was observed for higher doses and exposure time (increased lipid peroxidation, LPO). AgNO3 exposure caused impairment in GPx and glutathione-S-transferase (GST), probably as result of the higher bioavailability of Ag in the salt-form. The current results indicate that effects are partly caused by Ag ions released from Ag-NPs, but specific particle effects cannot be excluded. Highlights: Oxidative stress of Ag-NPs and AgNO3 was assessed in Eisenia fetida . Both Ag forms induced oxidative damage (LPO) via different mechanisms. Ag-NPs activated total glutathione, followed by GPx and GR. AgNO3 impaired GPx and GST. Overall results indicated effects from Ag ionization and NPs specific effects. Abstract : Oxidative stress to Ag in Eisenia fetida occurs via different mechanisms for Ag nanoparticles and AgNO3 .